(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Introduction Alcohol dependence Syndrome (ADS) frequently co-occurs with depressive disorder. Studies on quality of life among patients of ADS with and without co-occurring depressive disorder are limited. The current study aimed to compare quality of life among the two groups and to assess the correlation of severity of alcohol dependence and severity of depression with QOL. Methods It was a cross-sectional study with purposive sampling conducted among 60 (30 in each group) inpatient treatment- seeking male patients at a tertiary-level hospital in India. Instruments used included a semi-structured questionnaire, Revised Clinical Institute Withdrawal Assessment for Alcohol scale, Mini-International Neuropsychiatric Interview, Severity of Alcohol Dependence Questionnaire, WHO Quality of Life BREF scale, and Patient Health Questionaire-9. Descriptive statistics, group comparisons, and Pearson’s correlation were done. Results QOL was significantly poorer in treatment-seeking male patients with ADS with depressive disorder in physical (36.54, 95% CI: 3.95-21.46), psychological (28.55, 95%CI: 16.93-33.34), social (35.64, 95%CI: 0.59-26.46) and environmental (53.85, 95%CI: 4.91-18.96) domains than those without depressive disorder (49.25, 95% CI:3.95-21.46),(53.69, 95% CI:16.93-33.34), (49.16, 95%CI: 0.59-26.46),(65.78 95%CI: 4.91-18.96) respectively. Severity of alcohol dependence was significantly negatively correlated to physical domain of QOL in both the groups (p= 0.001), but it did not differ between two groups. Severity of depression was significantly negatively correlated to physical (p=0.01) & psychological (p=0.04) domains of QOL in patients with ADS with depressive disorder. Conclusion Prevention and treatment of alcohol dependence and national alcohol policy in India in the future should focus on early diagnosis and treatment of both depressive disorder and alcohol dependence to improve their quality of life.